A New Paradigm of Civil Liability for Damages Caused by AI Systems under Article 1365 of the Indonesian Civil Code - Pratidina, Ginung (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The revolution of Artificial Intelligence (AI) has presented fundamental challenges to the classical civil law framework, particularly Article 1365 of the Indonesian Civil Code (KUHPerdata), which is grounded in the concept of